2012
DOI: 10.1097/ajp.0b013e318232cddc
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction After Anterior Cervical Discectomy and Fusion Is Primarily Driven by Relieving Pain

Abstract: Improvement in pain seemed to be most important aspect in ACDF patients regarding the subjective SQ. Therefore, we strongly recommend focusing on pain-reducing therapies when choosing treatment for these patients during the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 24 publications
5
34
1
3
Order By: Relevance
“…Such factors may influence a global perceived effect (recovery) score, but do not necessarily describe good functioning or a good daily life. The results of the present study are in line with a previous study which showed that pain reduction was the strongest influence on satisfaction with ACDF surgery (143). Patients' ratings of effect of surgery after ACDF has also been proposed to overestimate positive results (144), indicating that an accurate evaluation of the extent to which the patients' problems are resolved by surgery requires questions regarding symptoms rather than only one general outcome score.…”
Section: Women's Experiences Of Daily Lifesupporting
confidence: 90%
“…Such factors may influence a global perceived effect (recovery) score, but do not necessarily describe good functioning or a good daily life. The results of the present study are in line with a previous study which showed that pain reduction was the strongest influence on satisfaction with ACDF surgery (143). Patients' ratings of effect of surgery after ACDF has also been proposed to overestimate positive results (144), indicating that an accurate evaluation of the extent to which the patients' problems are resolved by surgery requires questions regarding symptoms rather than only one general outcome score.…”
Section: Women's Experiences Of Daily Lifesupporting
confidence: 90%
“…Hessler et al 12 reported that 62% of the patients with motor deficit completely recovered after surgery. The rate of complete recovery in this study was much higher than that reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…Motor deficit can lead to disabilities, and some studies have reported that 78.4% of such patients showed an improvement in motor function and 21.6% showed neither improvement nor impairment even after surgery. 12 Patients with motor deficit require early surgical intervention; however, only a few studies aimed directly at establishing the choice and timing of treatment have been performed. If the risk factors for motor deficit and its prognosis can be clarified, the treatment should be initiated at an early stage.…”
mentioning
confidence: 99%
“…[1][2][3][4] Despite high success rates following ACDF, the risks for pseudarthrosis and adjacent segment disease have raised questions regarding its role as the first-line surgical treatment for cervical degenerative disease. [5][6][7][8][9] The fusion of cervical vertebrae is thought to reduce motion at the operated level, increasing stress on adjacent cervical disc levels.…”
Section: Introductionmentioning
confidence: 99%